The geochemistry of redox sensitive trace metals in sediments - Morford, J. L.; Emerson, S. (Geochimica Et Cosmochimica Acta, 1999)
We analyzed the redox sensitive elements V, Mo, U, Re and Cd in surface sediments from the Northwest African margin, the U.S. Northwest margin and the Arabian Sea to determine their response under a range of redox conditions. Where oxygen penetrates 1 cm or less into the sediments, Mo and V diffuse to the overlying water as Mn is reduced and remobilized. Authigenic enrichments of U, Re and Cd are evident under these redox conditions. With the onset of sulfate reduction, all of the metals accumulate authigenically with Re being by far the most enriched. General trends in authigenic metal accumulation are described by calculating authigenic fluxes for the 3 main redox regimes: oxic, reducing where oxygen penetrates less than or equal to 1 cm, and anoxic conditions. Using a simple diagenesis model and global estimates of organic carbon rain rate and bottom water oxygen concentrations, we calculate the area of sediments below 1000 m water depth in which oxygen penetration is less than or equal to 1 cm to be 4% of the ocean floor. We conclude that sediments where oxygen penetrates less than or equal to 1 cm release Mn, V and Mo to seawater at rates of 140%-260%, 60%-150% and 5%-10% of their respective riverine fluxes, using the authigenic metal concentrations and accumulation rates from this work and other literature. These sediments are sinks for Re, Cd and U, with burial fluxes of 70%-140%, 30%-80% and 20%-40%, respectively, of their dissolved riverine inputs. We modeled the sensitivity of the response of seawater Re, Cd and V concentrations to changes in the area of reducing sediments where oxygen penetrates less than or equal to 1 cm. Our analysis suggests a negligible change in seawater Re concentration, whereas seawater concentrations of Cd and V could have decreased and increased, respectively, by 5%-10% over 20 kyr if the area of reducing sediments increased by a factor of 2 and by 10%-20% if the area increased by a factor of 3. The concentration variations for a factor of 2 increase in the area of reducing sediments are at about the level of uncertainty of Cd/Ca and V/Ca ratios observed in foraminifera shells over the last 40 kyr. This implies that the area of reducing sediments in the ocean deeper than 1000 m (4%) has not been greater than twice the present value in the recent past. Copyright (C) 1999 Elsevier Science Ltd.
227ktTimes Cited:455Cited References Count:92